CHESS COMPOSITION AS A TEACHING TOOL: RETRACTORS AND RETROGRADE ANALYSIS - Dragan Martinović; Ivan J. Marković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
Chess composition is an integral part of the chess as an elective subject syllabi for older school children (5th to 8th grade) in Serbian primary schools. Retractor problems and retrograde analysis are also among the introduced contents (in addition to orthodox problems and studies), which represents a novelty in the process of chess education in primary schools. The introduction of these contents was tested during elective chess courses at the Teacher Training Faculty and the Faculty of Sport and Physical Education in Belgrade, as well as during seminars organized by the Institute for Advancement of Education and Upbringing in Belgrade. Both the current and the future chess teachers were very successful, with overly optimistic views regarding the prospective effects of the introduction of the new contents in the classroom practice. This paper covers only the first part of the research, which has yet to be completed by obtaining the complementary feedback from pupils (they still lack the necessary knowledge for this level of training). Therefore, final considerations should be postponed and remain inconclusive at present